Captivity restructures the gut microbiota of François' langurs (Trachypithecus francoisi) - Mo, Fengxiang; Li, Yuhui; Liu, Zheng; Zheng, Jingjin; Huang, Zhonghao (Frontiers in Microbiology, 2023)
Gut microbiota is crucial to primate survival. Data on gut microbiota of captive and wild animals can provide physiological and ecological basis for conservation of rare and endangered species. To study the effect of captivity on gut microbiota, we examine the difference in the gut microbiota composition between the captive and wild Francois’ langurs (Trachypithecus francoisi), using 16S rRNA sequencing technology. The results showed that the composition of gut microbiota of captive and wild langurs were characterized by Firmicutes (51.93% ± 10.07% VS 76.15% ± 8.37%) and Bacteroidetes (32.43% ± 10.00% VS 4.82% ± 1.41%) at the phylum level and were featured by Oscillospiraceae (15.80% ± 5.19% VS 30.21% ± 4.87%) at the family level. The alpha diversity of gut microbiota in captive langurs were higher than those in wild, such as Shannon index (4.45 ± 0.33 VS 3.98 ± 0.19, P < 0.001) and invSimpson index (35.11 ± 15.63 VS 19.02 ± 4.87, P < 0.001). PCoA results showed significant differences in the composition of gut microbiota between captive and wild langurs at both phylum and family level (weight UniFrac algorithm, phylum level: R2 = 0.748, P = 0.001, family level: R2 = 0.685, P = 0.001). Captive langurs’ relative abundance of Firmicutes (51.93% ± 10.07%) was lower than that of wild langurs (76.15% ± 8.37%), and the Bacteroides (32.43% ± 10.00%) was higher than that of the wild (4.82% ± 1.41%). Our study concludes that dietary composition could be crucial determinant shaping gut microbiota of langurs, because more fiber-rich foods used by the wild langurs could make the abundance of Firmicutes increase, and more simple carbohydrates-rich foods eaten by the captive langurs make the Bacteroidetes increase. We highlight the importance of captivity on the gut microbiota and the need to consider the gut microbiota in animal provision.